Psychological Immunity and Motivation for Achievement among university students in the light of the Corona pandemic (field study on a sample of students of Tishreen university) - زهره, نورا; سهير حلوم (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to identifying the relationship between Psychological Immunity and its relation with Achievement Motivation among the students of tishreeen university, and to know the differences between psychological immunity and the motivation of achievement according to the variables (gender and specialization). the sample consisted of (234) students from Tishreen university. The researcher’s used the psychological immunity scale which it was developed and adapted to context by AL SHARIF (2015). The researcher’s also used the Achievement motivation scale, and was developed and adapted to context by KALIFA (2012). The results showed that: 1-there was a positive correlation between the degrees of students in Psychological Immunity scale and their degrees in the Achievement motivation scale 2- there were statistically significant differences between the mean scores of males and the mean scores of females in the Achievement motivation scale in favor of females, while there were no differences between them in Psychological Immunity. 3- the existence of a statistically significant differences between theoretical colleges and applied colleges in the motivation Achievement in favor of theoretical colleges while there was no difference between them in psychological immunity.